Respuesta :

Answer:

x = ± [tex]\frac{\sqrt{5} }{3}[/tex]

Step-by-step explanation:

Given

3x² + 2[tex]\sqrt{5}[/tex] x - 5 = 0 ( add 5 to both sides )

3x² + 2[tex]\sqrt{5}[/tex] x = 5

Before completing the square we require the coefficient of the x² term to be 1

Factor out 3 from each term on the left side

3(x² + [tex]\frac{2\sqrt{5} }{3}[/tex] x ) = 5

To complete the square

add/ subtract ( half the coefficient of the x- term)² to x² + [tex]\frac{2\sqrt{5} }{3}[/tex] x

3(x² + 2( [tex]\frac{\sqrt{5} }{3}[/tex] )x + [tex]\frac{5}{9}[/tex] - [tex]\frac{5}{9}[/tex] ) = 5

3(x + [tex]\frac{\sqrt{5} }{3}[/tex] )² + ( 3 × - [tex]\frac{5}{9}[/tex] ) = 5

3(x + [tex]\frac{\sqrt{5} }{3}[/tex] )² - [tex]\frac{5}{3}[/tex] = 5 ( add [tex]\frac{5}{3}[/tex] to both sides )

3(x + [tex]\frac{\sqrt{5} }{3}[/tex] )² = [tex]\frac{20}{3}[/tex] ( divide both sides by 3 )

(x + [tex]\frac{\sqrt{5} }{3}[/tex] )² = [tex]\frac{20}{9}[/tex] ( take the square root of both sides )

x + [tex]\frac{\sqrt{5} }{3}[/tex] = ± [tex]\sqrt{\frac{20}{9} }[/tex] = ± [tex]\frac{2\sqrt{5} }{3}[/tex] ( subtract [tex]\frac{\sqrt{5} }{3}[/tex] from both sides )

x = - [tex]\frac{\sqrt{5} }{3}[/tex] ± [tex]\frac{2\sqrt{5} }{3}[/tex]

Thus

x = - [tex]\frac{\sqrt{5} }{3}[/tex] - [tex]\frac{2\sqrt{5} }{3}[/tex] = - [tex]\frac{\sqrt{5} }{3}[/tex]

x = - [tex]\frac{\sqrt{5} }{3}[/tex] +[tex]\frac{2\sqrt{5} }{3}[/tex] = [tex]\frac{\sqrt{5} }{3}[/tex]